The Influence of the Cooperative Learning Model PQ4R Type Containing Science Literacy on Students Learning Competencies of Ecosystem Material at SMA Negeri 1 Baso - Ayu Lestari; Rahmawati Darussyamsu; Siska Farma; Syamsurizal Syamsurizal (Universitas Negeri Padang, 2019)
Problems of the research that exist at SMA Negeri 1 Baso, student learning competencies were still low. The effort that can be done was to apply the cooperative learning model with the PQ4R type with science literacy content of SMA Negeri 1 Baso. The purpose of this research was to study student learning through a cooperative model of PQ4R type with science literacy content at SMA Negeri 1 Baso. This type of research was experimental research with randomized posttest control group design. The population in this study were all students of class X MIPA SMA 1 Baso registered in 2018/2019. Sampling was done using the Simple purposive Sampling technique, which was chosen as the research samples were class X MIPA 1 as the experimental class and X MIPA 3 as the control class. The instrument used consisted of posttest questions for knowledge competency, observation sheets for students attitudes and skills. The assessment hypothesis using the t-test, can prove the knowledge competency tcount 4.09> ttable1.67, competency assessment value 86% with very good categories for experimemt class and 58% with enough categories for control class. Competency of skill value tcount 3.55> ttable 1.67. This was an accepted hypothesis. Thus, It was concluded that the cooperative model of PQ4R type with science literacy content improve the competency of knowledge, attitude, and skill of class X MIPA students of SMA Negeri 1 Baso.